2004
DOI: 10.1253/circj.68.220
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Glucose Metabolism Assessed by Positron Emission Tomography and the Histopathologic Findings of Microvessels in Syndrome X

Abstract: Background Syndrome X has been recognized as a disease that is primarily reflected in the cardiac microvasculature. Myocardial metabolism in this condition has been studied, but not in relation to small vessel pathology. Methods and ResultsIn order to examine the relationship between myocardial metabolism and small vessel pathology, 24 consecutive patients with syndrome X (7 men, 17 women; mean age 58 years) were evaluated by the thallium exercise stress test, positron emission tomography using F-18 fluoro-deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Further insight into the pathophysiology of CMD was provided by Satake et al ., who noted increased myocardial 18 F fluoro-deoxyglucose (FDG) uptake in 24 subjects (17 women) with CMD undergoing FDG PET as compared to 11 controls [56]. Endomyocardial biopsy in these subjects revealed significant increase in smooth muscle cells and thickening of the vascular wall, even in capillary vessels and the small vessel lumen was markedly narrowed.…”
Section: Non-invasive Testingmentioning
confidence: 99%
“…Further insight into the pathophysiology of CMD was provided by Satake et al ., who noted increased myocardial 18 F fluoro-deoxyglucose (FDG) uptake in 24 subjects (17 women) with CMD undergoing FDG PET as compared to 11 controls [56]. Endomyocardial biopsy in these subjects revealed significant increase in smooth muscle cells and thickening of the vascular wall, even in capillary vessels and the small vessel lumen was markedly narrowed.…”
Section: Non-invasive Testingmentioning
confidence: 99%
“…Increases in the generation of proinflammatory cytokines, cell adhesion molecules, and growth factors can elicit inflammatory and proliferative changes in the vessel walls, resulting in microvascular dysfunction. 6,7 In this study, we attempted to determine whether total serum antioxidant status, as well as the levels of C-reactive protein (CRP) and monocyte chemotactic protein-1 (MCP-1), might be associated with cardiac syndrome X.…”
mentioning
confidence: 99%
“…Recently, Zhao et al [33] have demonstrated that cardiomyocyte ATP depletion directly leads to hyperpolarization of neighbouring microvascular SMC via gap junctions, reducing intracellular Ca 2+ levels and causing vasorelaxation to increase myocardial blood flow. Whether gap junctions are inhibited in CMD in microvascular SMC has yet to be determined; however, gap junctions between cardiomyocytes and endothelial cells are depleted in CMD in a diabetes setting [34] . It is possible that a similar depletion occurs with SMC in CMD, leading to defects in vasorelaxation.…”
Section: Vasoconstriction and Vasorelaxationmentioning
confidence: 99%